PENDIDIKAN SEKS DI KALANGAN PELAJAR SMA DI KOTA PADANG (Kasus: SMA yang Mendapat Program PIK-Remaja) - Kamita, Wiwit; Maihasni, Maihasni; Rahmad, Darmairal (Pendidikan Sosiologi, 2013)
Rampant sexual behavior that occurred among black students into the record, both the government and education. Various attemps have been made to overcome these problems. One of them is the implementation of sex education programs contained in PIK Youth (Adolescent Counseling Information Center). PIK Youth is a program of, by and for teens to obtain information about reproductive health. This study aims to describe how the implementation of sex education among high school students and what is being done to optimize the sex education. Research is located in the city of padang, precisely in high school with PIK Youth in category âuprightâ and performed from July through September 2013.Â Reality in this study were analyzed with the structuration theory by Anthony Giddens. This study uses a qualitative approach with descriptive type. Informants retrieval technique is done by sampling purposive, the number of informants by 22 people. Type of data are the primary data and secondary data. Techniques of data collection is done by method of observation and interviews with the unit of analysis is the individual. Data were analyzed using techniques Miles and Huberman in three stage, (1) the steps of reduction, (2) data presentation/analysis of data, and (3) drawing conclusions.Â Of research that has been conducted in four schools thet get PIK Youth program in the category âuprightâ, which consists of SMA Pertiwi 1, SMA N 12, SMK N 7 and SMA PGRI 3 Padang, researchers obtain results that revolues around the implementation of sex education material provision of sexuality, individual and group counseling, self development, life skill and rocurement seminars about health and reproductive health promotion and drug. Of the four schools, which makes PIK Youth activities as self development activities, such as in SMA Pertiwi 1 and SMAN 12 Padang and extracurricular activities such as in SMKN 7 and SMA PGRI 3 Padang. As for the efforts made in optimizing the school sex education is as follows: (1) The involvement of experts, (2) The establishment of peer community, (3) Incorporate material life skills and family life, and (4) Follow up.Â